Halal park 2.0: Organising halal production and supply networks - Tieman, Marco; Mohd Ridzuan, Darun (International Institute of Advanced Islamic Studies (IAIS), 2020)
The halal industry is expanding rapidly. Muslim consumer markets are today among the world’s fastest growing. Despite the significant size of the halal industry, however, which is growing in width (read: introducing new halal certifiable categories) and depth (read: more companies are embracing halal certification), there is an evident gap in meeting increased demand for high-quality halal consumer products. There is also a systemic shortage of halal-certified raw materials, other ingredients, and additives. As halal moves from a product approach towards a supply chain approach, issues of halal integrity have also come to the fore. Likewise, it remains problematic that multinationals from non-OIC countries dominate all halal categories, with only limited (and further diminishing) roles for companies from the Muslim world. There is also a total lack of horizontal and vertical collaboration in halal supply chains, leaving true halal synergy advantages on the table.